A systematic literature review of Intellectual Property Management in Higher Education Institutions. (2018)
Due to the new challenges faced by the Higher Education Institutions (HEIs) as generators of knowledge, the management of their Intellectual Property (IP) becomes relevant, in order to promote the obtaining of favorable results from the creations that are gestated with their resources and that are expected to be used by industry and society. Therefore, it has been interesting for some researchers to understand the complexity of these management systems. This paper exposes the state of the art of IP management in the Colombian context, supported by HEI cases in the world and Latin America. Among the main findings are: 1) a clear transition from the recognition of the importance of management to the proposal of management models, and 2) the need to deepen the definition of structures that support the complexity and particularity of an IES.